A coesão nominal e a conexão no gênero textual redação do ENEM produzido por alunos ingressantes no Ensino Médio - Dodó, Francisco Walisson Ferreira (2020)
This Thesis is located in the field of Applied Linguistics, above all, in the teaching and learning process of written production. Nominal cohesion and connection - in the light of Sociodiscursive Interactionism - in the writing of high school students are presented as our object of investigation. Our general objective is: to analyze the nominal cohesion and the connection in the production of the textual genre Enem Writing of high school students, considering the meaning effects of these cohesion mechanisms to guarantee the thematic progression. As specific objectives, we intend to: I) analyze how the types of nominal cohesion imply in the articulation and organization of the ideas of the texts produced by students entering high school; and II) to analyze the functions of connections in maintaining the thematic progression of the text produced by that same target audience, as well as the implications of these uses in writing. The key questions that will guide us in the investigation of these objectives are: I) what difficulties does the student entering high school face when producing cohesive texts, when he is subjected to writing dissertative-argumentative texts? E II) how does the student entering high school appropriate the linguistic-discursive elements materialized in nominal cohesion and connection and use them in essay-argumentative texts? To investigate the uses of these cohesive elements in the students' texts, we bring as our theoretical contribution the epistemology of Sociodiscursive Interactionism represented in the ideas of Bronckart (1999), since language, for him, must be understood as an activity that mediates social actions, allowing communication between the interactants from textual genres used in their specific production contexts. In addition to the ISD theory, to delve deeper into the characterization, description and definition of the types of nominal and connection cohesion, we turn to the studies proposed by: Bronckart (1999), Halliday & Hasan (1976), Beaugrande & Dressler (1981), Charolles (1997), Apothéloz (2003) and Adam (2011). In order to be able to account for our object of study, in our methodology, we used two important tools: Action Research (THIOLENT, 2011) and the Didactic Sequence (SCHNEUWLY; DOLZ, 2004), as we understand that, for the carrying out this work, we will not use these two tools only for data generation; since this research has an interventional character, we will act directly in the teaching and learning process, aiming to solve the problems diagnosed in the students' writing regarding the organization of the textual progression. In response to our first question, the data revealed that students had difficulties: I) in delimiting the theme; II) in organizing ideas, developing them and progressing the theme within the limits of the structure of the Enem Writing genre; III) deepening the theme; IV) to linguistically materialize important terms for the construction of meanings and, thus, better develop the theme; V) to articulate discursive topics; VI) using connectors between sentences and periods; VII) to properly use connectors; VIII) in addition to presenting truncations in construction of compound periods. Regarding our second question, the data revealed that: the resumes made with the use of locatives can be influenced by the context of text production; the uses of anaphors, in the text, not only represent the materialization of linguistic elements that take up a content, but can reveal different ways of constructing the intended meanings; in the Enem Writing genre, we observed a strong recurrence in the use, mainly, of associative anaphor; subsequently, the infidel, the faithful and the pronoun, which may suggest a singular characteristic of this genre and of its textual type; the effects of meaning constructed, by means of generic and specific remissive forms, in resumption of a content already said, using faithful, unfaithful, associative and pronominal anaphors, can suggest different forms of argumentative strategies; confirmation that nominal cohesion is a linguistic element that makes the text a connected whole; the use of unpreposited noun phrases can also act as a connection; textualization mechanisms (nominal cohesion and connection) both work for thematic progression and for the composition and structuring of the genre; the diversification of uses of connectives, in addition to representing a broad linguistic repertoire, may suggest different ways of constructing the argument; and, finally, the confirmation that the cohesive elements should be seen not only as linguistic-structural resources, but as elements that are at the service of the construction of argumentation in sociodiscursive practices, and may suffer influences from the context of production, depending on the roles represented by the interactants.